Skrining fitokimia dan uji aktivitas antibakteri ekstrak etanol daun kayu Jawa ((Lannea coromandelica) (Houtt) Merr terhadap bakteri Propionibacterium acnes dan Staphylococcus epidermidis - Munaziatul Jannah; Haris Munandar Nasution; M. Pandapotan Nasution; Yayuk Putri Rahayu (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Jawa wood (Lannea coromandelica) (Houtt.) Merr. is a tropical plant that has potential as a medicinal plant. Almost all parts of this plant can be used in traditional medicine. This wild plant can be found easily in various locations such as home gardens, roadsides and community gardens. This study aims to evaluate the potential antibacterial activity of ethanol extract from the leaves of Kayu Jawa (Lannea coromandelica) (Houtt.) Merr. Against the growth of Propionibacterium acnes and Staphylococcus epidermidis bacteria. This research used experimental methods involving sample collection, macroscopic examination, microscopic examination, simplicia making, characteristic examination, Phytochemical Screening, and Antibacterial Activity Test using ethanol extract from Kayu Jawa ((Lannea coromandelica) (Houtt) Merr) against the bacteria Propionibacterium acnes and Staphylococcus epidermidis, using the agar diffusion method. Macroscopic examination results show that the leaves of Kayu Jawa have a tapered shape with a total of 7-11 strands. The flowers produced are single and yellowish-green in color, while the fruit has seeds of a certain length. Microscopic examination reveals the upper epidermis, palisade fragments, coral flowers, and wooden vessels with thickened spirals and stairs. The characteristics of simplicia show a water content of 4%, soluble essence content in water 21%, soluble essence content in ethanol 23%, total ash content of 4.8%, and insoluble ash content of 0.4% acid. The results of phytochemical screening on simplicia powder and ethanol extract of Kayu Jawa leaves showed contents such as alkaloids, tannins, flavonoids, steroids/triterpenoids, saponins and glycosides. The antibacterial activity test showed that Jawa wood showed potential as an antibacterial agent, with different inhibitory abilities depending on the concentration used. At a concentration of 20%, an inhibition zone of 6.85 mm was observed against Propionibacterium acnes and 5.75 mm against Staphylococcus epidermidis. Meanwhile, at a concentration of 80%, the area of inhibition increased to 14.15 mm against Propionibacterium acnes and 11.75 mm against Staphylococcus epidermidis.